Citizen formation from the pedagogical potential of the studies of the territory (2011)
ABSTRACT: In Latin America, during the last 20 years, the political democratic project has become an achievable and desirable possibility to accomplish general wellbeing and hope for the population life quality improvement; to implement, constitute and strength such project towards this goal, the effective link of all the actors and their governmental, private, academic nongovernmental, social, civic, community and citizen life forces, is required within the territory where democracy is going to be implemented. Hence, for this democracy to be possible, it is indispensable to have individually and collectively thoughtful citizens, willing to exercise their citizenship, to build a democratic project and to possibly transform their reality. These citizens are not born, they are made and educated, rooted to the territory they inhabit, modify, and use and in which they set their social practices. The executed study suggests that in order to reach the citizen category, it is necessary, among other things, to appeal for the conscious processes theory, through the educational system, so that people, from early age, are allowed to know, understand, comprehend and put into practice citizen education potential as a pedagogical strategy to reach citizen status, exercise and promote citizenship and, strengthen a democratic political project. Emerging as so, the citizenship, territory and citizen education triad, pillar of the territorial citizen conception, essence of democratic consolidation.